Peningkatan Hasil Belajar Seni Rupa Menggunakan Model Project-Based Learning di Kelas IV SD Negeri 45 Bungo Pasang, Kota Padang - Khairatul Aini; Mansurdin Mansurdin (Universitas Negeri Padang, 2025)
This study aims to explain how the application of the Project-Based Learning (PjBL) model can lead to improved learning outcomes in visual arts education for fourth-grade students at SDN 45 Bungo Pasang, Padang City, integrated within the context of the Merdeka Curriculum. This Classroom Action Research employs a mixed-methods approach, combining qualitative and quantitative techniques. The research subjects are 19 fourth-grade students from SDN 45 Bungo Pasang during the January-June semester of the 2023/2024 academic year. The research findings include: First, the development of teaching modules in Cycle I showed an average percentage increase from 84.7% (B) to 95.8% (SB) in Cycle II. Second, the implementation of teaching from the teacher's perspective improved from 85,7% (B) in Cycle I to 94.7% (SB) in Cycle II. Third, the implementation of teaching from the students' perspective increased from 81,2% (B) in Cycle I to 94.7% (SB) in Cycle II. Fourth, student learning outcomes improved from an average of 72.6% (C) in Cycle I to 85.2 (B) in Cycle II. In conclusion, the PjBL model can enhance student learning outcomes in visual arts education for fourth-grade students at SDN 45 Bungo Pasang, Padang City.